Improvement of Physical Ability to Children Gymnasts in Tirana of Albania - Mara, Ferdinand (International Journal of Educational Studies, 2025)
Balance is one of the main physical components of the sport of gymnastics. This study aims to determine the improvement effect of balance in female gymnasts aged 6-8 years. Methodology: The study lasts for 16 weeks and includes 5 gymnasts of 6-8 years old. Training sessions take place six times a week, with duration of 2 hours for each session. The measurement of balance parameters is done at before and after of the experiment using the GRFP "Leonardo". Balance tests include the Romberg stand with eyes open and closed, semi-tangent stand with eyes open and closed, tangent stand with eyes open and eyes closed, one-legged stand with eyes open and with eyes closed. Results: The results are obtained for each test from GRFP; Std. Ellipse Area (cm 2); Std. Ellipse Angle (degree); Num. Eccentricity; dominant Freq (Hz); rel. Path length (mms); abs. Path length (mm); EQ(AP); Total Duration (s). Conclusion: The findings suggest that engaging in regular “Core Training” sessions can contribute to the development and improvement of balance skills in gymnasts of this age. Specific exercises aimed at core training have a direct impact on postural control and stability, which are essential for maintaining balance during various physical activities.